A review on metrics to measure and monitor the performance of strategy implementation - Okfalisa, Okfalisa (JATIT, 2009)
The strategy formulation in organizations will be useless unless it is well implemented. Monitoring and measuring the implementation process is responsibility of the stakeholders. By understanding the elements in strategy implementation such as the complexity of environment and dynamic changing in decision making can be considered as metrics to develop a performance tool and measurement kit. This metric mechanism can then deploy into a knowledge management system (Strategy Monitoring-Knowledge Management System). This paper explains the emerging metrics for measuring and monitoring strategy implementation at higher education institution in Malaysia. The concept of the balanced scorecard, the skandia navigator, the Okumus framework and the Cynafin framework will be used as the basic. The paper proposes a research framework in monitoring and measuring the success of strategy implementation and to ensure it aligns with organizational objectives.